Agro-ecological benefits of faba bean for rainfed Mediterranean cropping systems - Ruisi, Paolo; Amato, Gaetano; Badagliacca, Giuseppe; Frenda, Alfonso Salvatore; Giambalvo, Dario; Di Miceli, Giuseppe (Italian Journal of Agronomy, 2017)
This paper reviews the main results from a set of experiments carried out in a semiarid Mediterranean environment during the past 25 years on faba bean (Vicia faba L.), a crop traditionally grown in southern Italy and Sicily under rainfed conditions. These experiments focused on the residual effects of faba bean on subsequent crop(s) and assessment of the nitrogen (N) balance during the crop cycle, paying attention to both the environmental release of N (losses via volatilisation and denitrification) and estimates of N2 fixation as influenced by tillage system, intercropping, and presence/absence of mycorrhizal inoculum. Faba bean relied on N2 fixation more than other grain legumes typically grown in the Mediterranean region (e.g., chickpea). Contributing reasons were the higher plant N demand of faba bean and its lower capacity to use soil mineral N. This implies higher N benefits for subsequent crop(s) as well as higher risk of N losses from the plant–soil– atmosphere system via leaching, denitrification, and volatilisation. Results from these experiments contribute to better defining the role of faba bean in Mediterranean agro-ecosystems and to identifying technical solutions that maximise the potential benefits of faba bean as a fertility-building crop.